What is the role of TDP-43 in C9orf72-related amyotrophic lateral sclerosis and frontemporal dementia? - Scaber, J; Talbot, K (Oxford University Press, 2016)
The C9orf72 hexanucleotide repeat expansion mutation is the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), accounting for up to 12% of all patients in an average ALS clinic population. At post-mortem, patients with the C9orf72 hexanucleotide repeat expansion have the typical pathology seen in sporadic ALS and FTD, in which transactive response DNA-binding protein of 43kDa (TDP- 43; encoded by TARDBP) is translocated from its normal nuclear location to form cytoplasmic aggregates. However, they also show additional pathological features in the form of RNA foci, containing the transcribed hexanucleotide repeats, and aggregates, which stain with antibodies against dipeptide repeat proteins, the product of non-ATG translation. The order in which these distinct molecular abnormalities develop, and whether each of these pathological features is a necessary or sufficient condition for the development of clinical disease, are currently key questions in ALS/FTD research. In this issue of Brain, Vatsavayai et al. describe two strikingly different pathological cases of C9orf72-positive FTD with excellent ante-mortem characterization that provide novel and provocative contributions to this debate (Vatsavayai et al., 2016).